Child pages
  • CSU 290 (Spring 2008)

Versions Compared

Key

  • This line was added.
  • This line was removed.
  • Formatting was changed.

...

No Format
  (booleanp z) => (andp z t) = z
  (booleanp z) => (andp t z) = z
  (booleanp z) => (orp z nil) = z
  (booleanp z) => (orp nil z) = z

EDIT: Let me add the following properties that you can assume to.

No Format

  (booleanp z) => (andp z t) = z
  (booleanp z) => (andp t z) = z
  (booleanp z) => (orp z nil) = z
  (booleanp z) => (orp nil z) = z

(You can give a shot at proving these, but the proof is a bit different than what we're used to - it requires case analysis, that you can do using only Boolean reasoning. For now, just take the properties above as true. I will talk about the proof technique for this in some other entry below.)

...